ANALISIS LOGISTIK IKAN LAUT PT XYZ WILAYAH JABODETABEK DAN BANDUNG - Nurul Firdaus, Marimin dan Kirbrandoko (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Distribution system is part of a logistics system that has a major role for increase the company’slogistic cost. The increase of fuel prices, labor costs, and presence of traffic congestion in Jabodetabek andBandung area and also to determine the best alternative strategies which viewed from the estimated of thecompany’s required raw materials on each day, empty capacity of the truck, and also costs incurred on eachmonth. The determine the best alternative distribution strategies, raw material necessity forecasting are neededwhich will affect the entire capacity of the truck as well as the minimum spanning tree which used to determinethe most efficient alternative pathway. After simulation of the company’s distribution channel, then there arethree alternative distributions which incorporating with the different combination of pathways. Alternative Idetermined by changed the distribution channels of each company’s truck, alternative II determined by changedthe distribution channels based on the shortest distance of the main warehouse and unify all outlets both insideand outside Jabodetabek and Bandung area into one distribution pathway, and the alternative III determinedbased on the shortest distance from the main warehouse but separating outlets in outside Jabodetabek andBandung area into one group. Based on the environmental conditions in Jabodetabek and Bandung which havefrequent traffic congestion, the monthly required distribution cost, the empty capacity of each truck, andestimated company needs of marine fish, it can be stated that alternative II is deal alternative and can be usedby the company.Keywords: distribution cost, distribution system, forecasting, logistic system, minimum spanning tree